Identification of marine sand-dwelling dinoflagellates in Dinawan Island, Sabah - Al-Has, Asilah; Mohammad Noor, Normawaty (Universiti Malaysia Sabah, 2011)
Identification of marine sand-dwelling species is important due to the toxin-producing abilities of some species that may harm human beings. In this study, sand samples were collected for 12 months at Dinawan Island, Sabah. Samples were identified using light microscopy (LM) and Scanning Electron Microscopy (SEM). Sixteen dinoflagellates species have been identified including 4 potential toxic species i.e. Prorocentrum arenarium, P. lima, P. rhatymum and Amphidinium carterae. Prorocentrum norrisianum is morphologically very similar to P. cassabicum. List of sand-dwelling dinoflagellates species especially toxic species provides important knowledge for monitoring and management of harmful algal bloom.